Multiple treatment interruptions and protecting HIV-specific CD4 T cells enable durable CD8 T cell response and viral control - Jain, Anshika; Canepa, Gaspar E.; Liou, Mei-Ling; Fledderman, Emily L.; Chapoval, Andrei I.; Xiao, Lingzhi; Mukherjee, Ipsita; Balogun, Bushirat M.; Huaman-Vergara, Hellen; Galvin, Jeffrey A.; Kumar, Princy N.; Bordon, José; et al. (Frontiers in Medicine, 2024)
Human Immunodeficiency Virus (HIV) remains a global health challenge, and novel approaches to improve HIV control are significantly important. The cell and gene therapy product AGT103-T was previously evaluated (NCT04561258) for safety, immunogenicity, and persistence in seven patients for up to 180 days post infusion. In this study, we sought to investigate the impact of AGT103-T treatment upon analytical treatment interruptions (ATIs). Six patients previously infused with AGT103-T were enrolled into an ATI study (NCT05540964), wherein they suspended their antiretroviral therapy (ART) until their viral load reached 100,000 copies/mL in two successive visits, or their CD4 count was reduced to below 300 cells/μL. During the ATI, all patients experienced viral rebound followed by a notable expansion in HIV specific immune responses. The participants demonstrated up to a five-fold increase in total CD8 counts over baseline approximately 1–2 weeks followed by the peak viremia. This coincided with a rise in HIV-specific CD8 T cells, which was attributed to the increase in antigen availability and memory recall. Thus, the protocol was amended to include a second ATI with the first ATI serving as an “auto-vaccination.” Four patients participated in a second ATI. During the second ATI, the Gag-specific CD8 T cells were either maintained or rose in response to viral rebound and the peak viremia was substantially decreased. The patients reached a viral set point ranging from 7,000 copies/mL to 25,000 copies/mL. Upon resuming ART, all participants achieved viral control more rapidly than during the first ATI, with CD4 counts remaining within 10% of baseline measurements and without any serious adverse events or evidence of drug resistance. In summary, the rise in CD8 counts and the viral suppression observed in 100% of the study participants are novel observations demonstrating that AGT103-T gene therapy when combined with multiple ATIs, is a safe and effective approach for achieving viral control, with viral setpoints consistently below 25,000 copies/mL and relatively stable CD4 T cell counts. We conclude that HIV cure-oriented cell and gene therapy trials should include ATI and may benefit from designs that include multiple ATIs when induction of CD8 T cells is required to establish viral control.